Numeraktif: development of a numeracy activity book based on democratic parenting for elementary school students - Irfan Wahyu Prananto; Deswara Varen Ramadhani; Riyan Hidayat (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
Numeracy skills are a foundational component of primary education; however, national assessments indicate that Indonesian students' numeracy proficiency remains suboptimal. One often-overlooked factor in the development of numeracy learning materials is the role of parenting styles—particularly democratic parenting—which supports children’s autonomy and active participation in the learning process. This study aims to develop a numeracy activity book titled Numeraktif, grounded in the principles of democratic parenting, to enhance numeracy learning among primary school pupils. The research adopts a Research and Development (R&D) methodology, utilizing a simplified version of the Borg and Gall model, encompassing seven stages: preliminary study, planning, product draft development, expert validation, revision, limited trials, and final revision. Content and media experts conducted the validation process, while practicality and effectiveness were assessed through trials involving students, teachers, and parents. The validation results demonstrated a high level of feasibility, with an average score of 4.6. The practicality test yielded a score of 4.3, indicating the material’s usability and engagement value. Furthermore, the effectiveness test revealed a mastery level of 90%, underscoring the product's significant impact on improving students' numeracy skills. These results affirm that the Numeraktif activity book is both pedagogically sound and responsive to learners' psychosocial needs, presenting a promising and innovative approach to numeracy education in Indonesian primary schools.